For a Logic of Musical Improvisation.Reflections on the Relationship Between Original and Copy in Pareyson's Aesthetics (Itinera, 2015)
This essay aims at clarifying the relation between the notions of formativity and improvisation, with particular attention to musical practices. Firstly, I will focus on originality and exemplarity, then I will briefly deepen three themes of particular interest faced by Pareyson’s philosophy of art: 1) the unforeseen; 2) the interpretation; 3) the cue or sketch. My purpose is to suggest some adjustments to the notion of formativity, in order to outline the essential features of a logic of musical improvisation.